Predictive Capacity of Working Memory and Inhibition in Early Mathematical Skills - Bernal-Ruiz, Francisca (2023)
Early mathematical competencies have a great impact on academic performance and on the development of more complex mathematical skills, especially in early education. Several authors have highlighted the importance of working memory and inhibition in the development of these mathematical skills; however, there is no agreement regarding the explanatory capacity of these executive domains with respect to differentiated performance in mathematics. The aim of this research was to evaluate the predictive capacity of verbal and visuospatial working memory and of behavioral and cognitive inhibition in mathematical competencies of relational logic and numerical type in 106 Chilean children of early education between 4 and 6 years old, who were evaluated with four executive tasks and an early mathematical assessment test. For data analysis, correlations and multiple linear regressions were performed. The results showed that verbal working memory was a relevant predictor of both logical-relational and numerical mathematical competencies. These findings are relevant for the educational system, especially for early education, as they confirm that as children advance in their educational trajectory, their working memory is strengthened and with it their mathematical performance.